2009
DOI: 10.1007/978-3-642-03821-1_11
|View full text |Cite
|
Sign up to set email alerts
|

A Market-Based Approach to Multi-factory Scheduling

Abstract: Abstract. In this paper, we report on the design of a novel market-based approach for decentralised scheduling across multiple factories. Specifically, because of the limitations of scheduling in a centralised manner -which requires a center to have complete and perfect information for optimality and the truthful revelation of potentially commercially private preferences to that center -we advocate an informationally decentralised approach that is both agile and dynamic. In particular, this work adopts a marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We showed that our mechanism performs close to the optimal solution (as computed by a centralized optimizer), it deals adaptively with changing sensor numbers and topology, and it extends the useful life of the network by a factor of three over the traditional approach. Second, we consider work on developing strategies for auctions that allocate aircraft engines that require maintenance to repair and overhaul bases (Vytelingum et al, 2009). In this context, the structure of the electronic institution is fixed.…”
mentioning
confidence: 99%
“…We showed that our mechanism performs close to the optimal solution (as computed by a centralized optimizer), it deals adaptively with changing sensor numbers and topology, and it extends the useful life of the network by a factor of three over the traditional approach. Second, we consider work on developing strategies for auctions that allocate aircraft engines that require maintenance to repair and overhaul bases (Vytelingum et al, 2009). In this context, the structure of the electronic institution is fixed.…”
mentioning
confidence: 99%
“…Similar inter-firm cases can also be found in the airport ground handling service scheduling (Mao et al, 2009) and supply chain scheduling (Lau et al, 2006). In a distributed environment, the approach that respects the privacy of self-interested decision makers is preferable as stated in (Lau et al, 2006;Stranjak et al, 2008;Vytelingum et al, 2009), because decision makers may be potential competitors in the same marketplace.…”
Section: Distributed Multi-project Schedulingmentioning
confidence: 99%
“…start time, duration, resource requirements) is inevitably required by the mediator. Note that in a competitive environment, the project agent may still be unwilling to reveal its valuable sensitive information, even if the mediator is an automated agent (Vytelingum et al, 2009). Secondly, when the individual objective of each PA cannot be decomposed precisely to each activity (e.g.…”
Section: Other Approachesmentioning
confidence: 99%